2012
DOI: 10.1111/j.1475-6765.2012.02056.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissent in Iberia: The ideal points of justices on the Spanish and Portuguese Constitutional Tribunals

Abstract: In this article, the non-unanimous decisions of the Portuguese and Spanish Constitutional Tribunals for the periods 1989–2009 and 2000–2009 are analysed. It is shown that judicial dissent can be predicted moderately well on the basis of judicial ideal points along a single dimension. This dimension is equivalent to the left–right cleavage in both Portugal and Spain. The characteristics of the recovered dimension are demonstrated by analysing both the properties of the cases and the properties of the justices w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(40 citation statements)
references
References 21 publications
0
36
0
4
Order By: Relevance
“…The results of this study are also interesting when considered in light of recent evidence of the ideological basis of decision making by European constitutional courts (e.g., Hanretty ; Hönnige ). This line of research has demonstrated that courts strike government actions more often when the court consists of judges with conflicting ideological preferences to that of the government (Hönnige ).…”
Section: Resultsmentioning
confidence: 66%
“…The results of this study are also interesting when considered in light of recent evidence of the ideological basis of decision making by European constitutional courts (e.g., Hanretty ; Hönnige ). This line of research has demonstrated that courts strike government actions more often when the court consists of judges with conflicting ideological preferences to that of the government (Hönnige ).…”
Section: Resultsmentioning
confidence: 66%
“…Ideology has to be determined by other methods. The Martin-Quinn method has been used widely in the US and has also been applied in other countries including Canada (Alarie and Green (2009)), Portugal and Spain (Hanretty 2012), the UK (Hanretty 2013) and Argentina (Bertomeu et al 2017). As the ideal points do not really provide a reason for the alignment of judges, other information needs to be used to determine what causes the ordering (Epstein et al (forthcoming)).…”
Section: How To Measure Ideology?mentioning
confidence: 99%
“…For example, Hanretty 2012 examined the Portuguese and Spanish constitutional courts and found that voting could be predicted based on the ideal points of the judges, with their relative positions corresponding to a left-right spectrum.…”
Section: Ideology and Constitutional Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…This view is most prevalent in the United States, where "the issue of what drives judges is largely settled" (Helmke and Sanders, 2006, 867), and where sets of measurements of judicial preferences along the left-right dimension (Martin and Quinn, 2002) are to judicial politics what estimates of policy positions from manifestos are to the study of party politics. However, the claim that judges are policy-seekers with respect to the left-right dimension has also been made for judges on the French Conseil Constitutionnel and German Bundesverfassungsgericht (Hönnige, 2009), the Italian Corte Costituzionale (Dalla Pellegrina and Garoupa, 2013), and the Spanish and Portuguese Constitutional Tribunals (Hanretty, 2012). The claim that judges are policy-seekers with respect to other dimensions, in particular the centre-periphery dimension, has also been made for the European Court of Justice (Malecki, 2012) and the European Court of Human Rights (Voeten, 2008).…”
Section: Why Expect Political Judging?mentioning
confidence: 99%